(untitled) (Med Phoenix, 2024)
Introduction: Normal person can interpret colour in all three of its attributes; Hue, intensity, and saturation. Human beings can perceive three primary colours, that is, red, green, and blue. Any defect in appreciation of colours is known as colour vision deficiency (CVD). Blood groups are genetically inherited as well. The study was undertaken to find out the prevalence of CVD among school students in Duwakot and to find out its relation with ABO blood groups, as these two entities are both inherited genetically. Materials and Methods: Permission was taken from the Institutional Review Committee of KMC to conduct this study. The study was carried out among the 8th, 9th and 10th grade school students of Duwakot, Bhaktapur. Ishihara test plates for colour vision and agglutination method for ABO blood grouping were used to get the prevalence of CVD and to get the percentage of students belonging to ABO blood group among those having Colour Vision Deficiency. Results: It was found out that, out of 150 students, 133 (88.67%) were normal. 17 students (11.33 %) were having CVD. No one was found complete colour blind. Prevalence of blood group among study population was O (38%) which was followed by B (31.61%), A (23.33%) and AB (8.66%),respectively. All the defects were of red-green type, hence were transmissible genetically. Distribution of blood group in CVD subjects shows 9 (52.94 %) numbers belonging to blood group B, 4 (23.53%) belonging to blood group O, 3 (17.64 %) belonging to blood group AB, and 1 (5.8%) belonging to blood group A. Conclusion: The study helps the subjects to be aware of their condition early in their professional life so that they can choose correct profession. It also tried to find out the percentage distribution into ABO blood groups. A larger population should be included to get more accurate results.